HER2/neu revisited: quality and interpretive issues. Issue 2 (3rd December 2010) - Ahmed, Syed Salahuddin; Iqbal, Jabed; Thike, Aye Aye; Lim, Alvin Soon Tiong; Lim, Tse Hui; Tien, Sim Leng; Tan, Puay Hoon
Abstract : Background: Immunohistochemistry (IHC) and fluorescence in situ hybridisation (FISH) are the only tests currently approved by the US Food and Drug Administration for classifying which patients will benefit from trastuzumab therapy. The accuracy of these two testing methods can be adversely affected by a variety of pre-analytical, analytical and post-analytical factors. According to the latest published recommendations of the panel of the Joint Committee of the American Society of Clinical Oncology and College of American Pathologists for HER2/neu testing, laboratories performing IHC and FISH for HER2/neu status in breast cancer are now required to have a high concordance of at least 95% between IHC and FISH, significantly higher than that in the published literature. Aim: To perform a retrospective analysis of the concordance of IHC and FISH analysis for HER2/neu at Singapore General Hospital and review potential causes of disparity between these two methods. Method: A retrospective review of a total of 106 invasive ductal carcinomas evaluated for HER2/neu at the Department of Pathology, Singapore General Hospital between 2007 and 2008 were included in the study. The initial HER2/neu immunostained slides were reviewed independently without knowledge of FISH results, and concordance between IHC and FISH was determined. Results: Concordance between IHC and FISH assay was excellent and within the published range (104/106=98.1%). The discordant cases represent a well-recognised subset of genetic heterogeneity in HER2/neu, which is known to contribute to positive IHC and negative FISH tests.